Effects of Resistive Diaphragmatic Training on the Pulmonary Functions in patients with Chronic Stroke - Bushra Mushtaq, Hamna Afzal, Anum Aftab, Mushayaida Iqbal, Arooma Muzummil, Shafaq Altaf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Stroke is the leading cause of death and disability worldwide. It is a cerebrovascular disease, characterized by decreased blood supply to the brain tissues. It is known that patients with stroke have respiratory muscle weakness. Aim: To evaluate the effects of Resistive Diaphragmatic Breathing Exercises on the pulmonary functions in patients with chronic stroke. Method: A randomized controlled trial was conducted. 20 subjects were recruited based on inclusion and exclusion criteria and were allocated to Group A and B. Assessment of Pulmonary Functions was undertaken by Digital incentive Spirometer. Group A received treatment with Digital Incentive Spirometer. Group B received Digital Incentive Spirometer training and also inspiratory Muscle training (IMT), Diaphragmatic Breathing Exercises. 3 sessions per week for 4 weeks were given to each patient. The two groups were reassessed after 3 weeks of treatment. Follow up was taken 4 weeks after completion of treatment. Data was analyzed by using SPSS 21. Results: There was a statistically significant change within both groups in the VC, FVC, PEF, SPO2 and FEV1 and FEV1/FVC with p- value of < 0.05. Both were effective but using inspiratory Muscle training along with Digital incentive Spirometer training technique showed more improvement. Conclusion: Resistive Diaphragmatic breathing exercises found better than the simple spirometer training for improving the pulmonary functions. Resistance through Thera bands at the sternal and costal level have found the better results. Resistive Diaphragmatic breathing have better results in VC and FVC, FEV. These techniques if incorporated in early rehabilitation protocol of stroke patient helps in early discharge. Key words: Stroke, Inspiratory Muscle training, Spirometer training, diaphragmatic breathing